Penerapan Model Pembelajaran Discovery Learning Menggunakan Aplikasi Kahoot Terhadap Hasil Belajar Fisika Siswa Kelas X SMA Negeri 1 Kepenuhan Hulu - Betria Putri Syarita; Azmi Asra; Ika Daruwati (JURNAL PENDIDIKAN ROKANIA, 2025)
The low student learning outcomes in physics learning are due to the lack ofunderstanding that students have in learning which causes students to become passive. This research aims to determine the effect of the Discovery Learning (DL) learning using kahoot application to the physics learning outcomes of class X SMA Negeri 1 Kepenuhan Hulu students. This research uses quantitative methods with a type of pre-experimental research, namely one group pretest-posttest design. The population in this study were class X students of SMA Negeri 1 Kepenuhan Hulu. Determining the sample using the Purposive Sampling technique, the sample was obtained from class X1 students consisting of 20 students. The instrument used is a multiple choice test. Based on the research results, the average pretest score was 44.52, which was lower than the average posttest score of 86.42.To see the increase in learning outcomes, it can be seen based on the N-Gain calculation, which is obtained at 0.75 in the high category. So it can be concluded that there is an influence in improving student learning outcomes using the Discovery Learning learning using kahoot application to the physics learning in renewable energy.